A review on carbon nanotubes reinforced ceramic composite - Mohd Tobi, Abdul Latif (2015)
This review looks at carbon nanotubes (CNT) capabilities as toughening agent in ceramic composite. CNT have exceptional mechanical strength of up to 60 GPa and stiffness of 1 TPa. Ceramic however is hard, brittle and lack of toughness. CNT were found to be capable to provide up to 173% improvement in fracture toughness of ceramic with 19 vol.% CNT. The degree of toughness improvement on CNT ceramic composite is dependent on the following parameters; i) CNT homogenous dispersion in the composite, ii) inter-wall and interfacial strength between CNT and ceramic, iii) method of producing the CNT ceramic composite, and iv) the resultant toughening mechanisms.